Scattering Optimization of Photonic Cluster: From Minimal to Maximal Reflectance - V. V. Prosentsov (International Journal of Optics)
Scattering optimization is a challenging engineering problem with an extensive list of potential applications. For some practical applications, the reflectance of the photonic cluster should be variable from minimal to maximal values. The theoretical investigation of such problem is extremely difficult due to multiple interactions between particles in the cluster. In this paper, the optimization of the light scattered by the photonic cluster made of small particles is studied with the help of the special optimization algorithm and the local perturbation method. It was shown that the photonic cluster can be transformed in such a way that its reflectance will be increased or decreased by several orders of magnitude for selected wavelength and direction.